Misuse of Child Sexual Abuse Images: Treatment Course of a Self-Identified Pedophilic Pastor. Issue 3 (3rd April 2018) - Konrad, Anna; Amelung, Till; Beier, Klaus M.
ABSTRACT: The recurrent use of child sexual abuse images (CSAI) for sexual arousal is considered a valid indicator for the existence of a pedophilic preference, which in turn represents a significant risk factor for committing contact offenses against children. Treatment programs for (potentially) sexually delinquent men endeavor to reduce the risk to offend by addressing relevant risk factors and emphasizing functional and socially acceptable alternative behaviors. Users of CSAI are a particular target group for prevention services and it has been suggested that the primary treatment focus should be on sexual self-regulation deficits.